2018
DOI: 10.1029/2018jb015936
|View full text |Cite
|
Sign up to set email alerts
|

Magma Chamber and Crustal Channel Flow Structures in the Tengchong Volcano Area From 3‐D MT Inversion at the Intracontinental Block Boundary Southeast of the Tibetan Plateau

Abstract: Based on magnetotelluric (MT) array data, we have obtained the first three‐dimensional (3‐D) electrical resistivity model at the Gaoligong intracontinental block boundary in southeastern Tibetan Plateau where the Quaternary intraplate Tengchong volcanism and seismic activities occur. Comparing with results of previous geophysical studies in the area, our MT model clearly reveals three conductive bodies in the depth ranges of 10–30 km in the Tengchong volcano area, which we interpret as three middle‐lower crust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 49 publications
4
38
0
Order By: Relevance
“…Resistor R3 is surround by a ring‐shaped conductive structure beneath the GLGSZ. In fact, the R3 feature has already been imaged in the previous work of Ye et al (2018) and is further verified by this study. Ye et al (2018) revealed a complex pattern of crustal flow in the Gaoligong area.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Resistor R3 is surround by a ring‐shaped conductive structure beneath the GLGSZ. In fact, the R3 feature has already been imaged in the previous work of Ye et al (2018) and is further verified by this study. Ye et al (2018) revealed a complex pattern of crustal flow in the Gaoligong area.…”
Section: Discussionsupporting
confidence: 91%
“…Dong et al (2016) revealed two distinct quasi‐linear north to northeast conductive anomalies in the middle‐to‐lower crust near EHS separated by a large‐scale resistive structure extending from the crust to the upper mantle. Three‐dimensional (3‐D) MT array data in the Tengchong volcano area (Ye et al, 2018) suggested that there is no overall middle‐to‐lower crust flow in western Yunnan. Therefore, the conductive channels proposed in the previous two‐dimensional (2‐D) MT model are still controversial and require further study.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the depth range roughly corresponds to the penetration depths for MT data in the periods of 25-132 s. These features are strong indications for the occurrence of macroanisotropic bodies (Wannamaker, 2005), although these bodies could be interpreted as realistic structures (e.g., Zhang et al, 2016). Figure S17), which may indicate that MT anisotropy should be considered (Ye et al, 2018). The seismic radial anisotropy ξ is determined from the velocities of SH and SV waves as ξ = 2(V SH -V SV )/(V SH + V SV ) (e.g., Luo et al, 2013).…”
Section: Evidence For Anisotropymentioning
confidence: 59%
“…Furthermore, the depth range roughly corresponds to the penetration depths for MT data in the periods of 25–132 s. These features are strong indications for the occurrence of macroanisotropic bodies (Wannamaker, ), although these bodies could be interpreted as realistic structures (e.g., Zhang et al, ). Compared to the models inverted from Z + Tz (Figures and ) and Z only (Figure ), the model inverted from Tz only (Figure ) shows different electrical structures below 5 km between the Darbut and the Karamay‐Urho faults. Prominent differences are the resistivity contrast and spatial distribution of anomalies, which have also been reported by previous studies in the context of macroanisotropy (e.g., Kapinos et al, ). Corresponding to the area and depth range, strong seismic negative radial anisotropy is present (Figure S17), which may indicate that MT anisotropy should be considered (Ye et al, ). The seismic radial anisotropy ξ is determined from the velocities of SH and SV waves as ξ = 2(V SH – V SV )/(V SH + V SV ) (e.g., Luo et al, ).…”
Section: Evidence For Anisotropymentioning
confidence: 99%
“…The consistent strain field in the crust (inferred from Global Positioning System observations and focal mechanism solutions; Kreemer et al, ; Xu et al, ) and the upper mantle (inferred from teleseismic shear‐wave splitting (SKS) measurements; Huang, Wang, Xu, Ding, et al, ; Wang et al, ) supports vertically coherent lithospheric deformation. However, seismic and magnetotelluric tomography revealed extensive low‐velocity and high‐conductivity zones in the midlower crust (Bai et al, ; Bao et al, ; Wei et al, ; Yao et al, ; Ye et al, ), indicating a very weak deep crust that is incapable of vertical stress transfer between the crust and upper mantle. However, the coherent deformations in the upper crust and mantle lithosphere could also be achieved as well by the same boundary force laterally in spite of a weak deep crust in between (Huang et al, ; Wang et al, ).…”
Section: Introductionmentioning
confidence: 99%